Peran Dana Desa dalam Pembangunan Sarana dan Prasarana Desa di Kabupaten Kediri - Achsina Hawa Ilmiawan; Alfinda Sallimma Syafitri; Alda Melinda; Helyanifa Gadistriani (OPTIMAL Jurnal Ekonomi dan Manajemen, 2026)
This study aims to examine and analyze the role of Village Funds in the development of infrastructure and public facilities in Gedangsewu Village, Pare Subdistrict, Kediri Regency. The research is motivated by the importance of Village Funds as a key instrument for community-based development and the improvement of rural welfare. A qualitative descriptive approach was employed, with data collected through field observations, in-depth interviews with village officials and community members, and a review of planning documents and financial reports. The findings indicate that Village Funds have made a significant contribution to the development of various village facilities and infrastructure, including roads, bridges, irrigation systems, religious facilities, and sanitation programs. Village Fund management is carried out through village deliberations, needs-based planning, transparent and accountable financial management, and regular coordination among village authorities. However, the implementation of development programs still faces several challenges, such as regulatory changes, budget limitations, and bureaucratic constraints. Community participation plays a crucial role in supporting the success, sustainability, and effectiveness of village development. Overall, the utilization of Village Funds has improved mobility, economic productivity, and the quality of life of the people of Gedangsewu Village.